2015
DOI: 10.1159/000381326
|View full text |Cite
|
Sign up to set email alerts
|

Normal-Appearing Endometrial Cells in Pap Tests of Women Aged Forty Years or Older and Cytohistological Correlates

Abstract: Objective: The Bethesda System 2001 for reporting cervical cytology recommends reporting benign-appearing, exfoliated endometrial cells in women aged 40 years or older. The objective of this study was to determine the significance of normal endometrial cells in conventional Papanicolaou (Pap) tests of women aged 40 years and older and to correlate this finding with histological follow-up. Study Design: Over a period of 5 years, all Pap tests showing endometrial cells in women aged ≥40 years were identified. Hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 24 publications
0
7
0
2
Order By: Relevance
“…We defined abnormal cytology more strictly as the presence of atypical glandular cells or EC cells, whereas Roelofsen et al included the presence of endometrial cells into abnormal cervical cytology . Categorization of the presence of endometrial cells into normal cervical cytology is supported by recent data of Izadi‐Mood et al, 25 who demonstrated in a series of 199 cases that the presence of endometrial cells in cervical cytology tests of women older than 40 years was not associated with significant endometrial lesions …”
Section: Discussionmentioning
confidence: 75%
“…We defined abnormal cytology more strictly as the presence of atypical glandular cells or EC cells, whereas Roelofsen et al included the presence of endometrial cells into abnormal cervical cytology . Categorization of the presence of endometrial cells into normal cervical cytology is supported by recent data of Izadi‐Mood et al, 25 who demonstrated in a series of 199 cases that the presence of endometrial cells in cervical cytology tests of women older than 40 years was not associated with significant endometrial lesions …”
Section: Discussionmentioning
confidence: 75%
“…Slične probleme navode i drugi autori. 21,24,28,29 Jedno stavna hiperplazija endometrija točno je dijagnostici rana kod 11 od 13 bolesnica (84,6%), a kompleksna hiperplazija samo u njih 50% (2/4) (slika 3.). Katkad se degenerativne promjene endometrijskih stanica poput, npr., povećanja jezgara mogu interpretirati kao atipija.…”
Section: Raspravaunclassified
“…Slične rezultate navode i drugi autori. 15,21,[24][25][28][29] S obzirom na sve širu i opsežniju uporabu histero skopskih zahvata u dijagnostici endometrijskih pore mećaja, na trenutak se čini da citologija endometrija nema kliničku svrhu. Ipak, to nije točno.…”
Section: Raspravaunclassified
“…I read with interest the recently published article entitled ‘Normal-appearing endometrial cells in Pap tests of woman aged forty years or older and cytohistological correlates' by Izadi-Mood et al [1]. They report that the incidence of clinically significant endometrial lesions associated with the presence of endometrial cells (EMC) in Papanicolaou (Pap) tests of women aged 40 years and older was very low and suggest endometrial sampling only when additional clinical indicators are present.…”
Section: Tablementioning
confidence: 99%